Combining PPB and marker-assisted selection: strategies and experiences with rice - Steele, K; Virk, D; Prasad, S; Witcombe, John R. (International Plant Genetic Resources Institute, 2002)
Participatory plant breeding should not preclude the use of modern biotechnological techniques.